Pigment-protein complexes are organized into stable microdomains in cyanobacterial thylakoids - Strašková, A; Steinbach, G; Konert, G; Kotabová, E; Komenda, J; Tichý, M; Kaňa, R (Biochimica et biophysica acta. Bioenergetics, 2019)
Thylakoids are the place of the light-photosynthetic reactions. To gain maximal efficiency, these reactions are conditional to proper pigment-pigment and protein-protein interactions. In higher plants thylakoids, the interactions lead to a lateral asymmetry in localization of protein complexes (i.e. granal/stromal thylakoids) that have been defined as a domain-like structures characteristic by different biochemical composition and function (Albertsson P-Å. 2001,Trends Plant Science 6: 349-354). We explored this complex organization of thylakoid pigment-proteins at single cell level in the cyanobacterium Synechocystis sp. PCC 6803. Our 3D confocal images captured heterogeneous distribution of all main photosynthetic pigment-protein complexes (PPCs), Photosystem I (fluorescently tagged by YFP), Photosystem II and Phycobilisomes. The acquired images depicted cyanobacterial thylakoid membrane as a stable, mosaic-like structure formed by microdomains (MDs). These microcompartments are of sub-micrometer in sizes (~0.5-1.5 μm), typical by particular PPCs ratios and importantly without full segregation of observed complexes. The most prevailing MD is represented by MD with high Photosystem I content which allows also partial separation of Photosystems like in higher plants thylakoids. We assume that MDs stability (in minutes) provides optimal conditions for efficient excitation/electron transfer. The cyanobacterial MDs thus define thylakoid membrane organization as a system controlled by co-localization of three main PPCs leading to formation of thylakoid membrane mosaic. This organization might represent evolutional and functional precursor for the granal/stromal spatial heterogeneity in photosystems that is typical for higher plant thylakoids.
Keywords: fykobilizomy; Cyanobacteria; Photosystems; Synechocystis; zobrazování trojrozměrné; Imaging, Three-Dimensional; bakteriální proteiny; Thylakoids; Bacterial Proteins; fotosystém I (proteinový komplex); Phycobilisomes; Photosynthesis; Confocal microscopy; membránové mikrodomény; tylakoidy; Photosystem II Protein Complex; fotosyntéza; fotosystém II (proteinový komplex); Membrane heterogeneity; Membrane Microdomains; Thylakoid membrane; Microscopy, Confocal; konfokální mikroskopie; Microdomains; Population heterogeneity; Photosystem I Protein Complex